Control of hydrogen and carbon impurity inclusion during the growth of GaAsN thin film by atomic layer epitaxy. (16th December 2015) - Yokoyama, Yuki; Fukuyama, Atsuhiko; Haraguchi, Tomohiro; Yamauchi, Toshihiro; Ikari, Tetsuo; Suzuki, Hidetoshi
Abstract: The effects of growth temperature and nitrogen (N) source duration on N, carbon (C), and hydrogen (H) concentrations in GaAsN layers grown by atomic layer epitaxy (ALE) were investigated to understand the incorporation mechanisms of these atoms. In addition, the effects of the above growth conditions on the self-limiting mechanism (SLM) were investigated. The SLM was in effect at growth temperatures of 500 and 520 °C. The origin of the residual C was not N but other sources. With increasing N source duration, the N and H concentrations increased and saturated. The N incorporation mechanisms were discussed by a simple model considering the absorption and desorption of N atoms on the gallium (Ga)-covered surface. H atoms originating from the N source were incorporated in to the GaAsN layer. According to the ratio of the H concentration to the N concentration, the difference in the incorporation processes of N and H atoms in ALE-grown GaAsN layers was discussed.